MAKING POLICY FROM THE LANGUAGE: LINGUISTIC STANDARD AND CITIZEN CONSTRUCTION IN A PROVINCE NEWSPAPER - Baretta, Mónica (Revista de Historia Social y de las Mentalidades, 2022)
This article focuses on the analysis of El Colono del Oeste, a weekly newspaper published between 1878 and 1886 in the province of Santa Fe (Argentina). The interest is in pointing out that, as a discourse and as a sociolinguistic object, the newspaper established guidelines for political and citizen participation in a culturally and linguistically diverse community. Thus, it will be analyzed the way in which, through the use of Spanish and the marking of the linguistic norm, El Colono del Oeste configured its audiences and placed them in the public space.